Analisis Penerapan Green Accounting pada RSUD Kota Mataram - Julia Rospani, Tika Wahyu; Handajani, Lilik (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
The aim of this research is to find out how green accounting is implemented at the Mataram City Regional Hospital as a prevention effort. This research uses a qualitative descriptive methodology with data collection tools in the form of observation, interviews and documentation. The results of this research indicate that the Mataram City Regional Hospital has incurred waste management costs. Mataram City Hospital has implemented environmental accounting starting from the identification, recognition, measurement, presentation and disclosure sections.